NYENTANA: SISTEM PERKAWINAN SUKU BALI DI DESA URASO KECAMATAN MAPPEDECENG KABUPATEN LUWU UTARA - Abdul Rahman (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2023)
The factors that led to the process of implementing the nyetana marriage in Uraso Village, namely: first, the naur sesangi factor (giving thanks by keeping promises); the two matchmaking factors; nyentana marriage which is the opposite of an ordinary marriage, nyentana marriage whose function is to continue as a successor in the woman's house where the obligations in the woman's house will be carried out by the man who carries out the nyentana marriage, and also the man can do his swadarma in the woman's house, where in matters of sanggah (place of worship at home) and pura (place of public worship) the main goal is also that later her wife's parents die she is obliged to carry out the cremation ceremony for both parents. In a nyentana marriage, the man who enters into the marriage does not have the right to inheritance where all inheritance is handed over to his wife and on behalf of his wife, in this case from the man who is nyentana, does not also have the right to custody of his child if there is a conflict in his household. . The position of men here does not have any rights if there is a divorce in a nyentana marriage.